Short courses of antimicrobial therapy for bacterial vaginosis: the possibilities of modern pharmacology: A review - Evgenia V. Shikh; Natalia B. Lazareva; Tatyana M. Ponomarenko (IP Berlin A.V., 2022)
Bacterial vaginosis is associated with severe infectious and inflammatory diseases and reduces the quality of life in women of reproductive age. Its worldwide prevalence is up to 80%. Thus, the development of new effective and safe methods of antimicrobial therapy becomes an urgent problem. This article provides a review of current antimicrobial therapies for bacterial vaginosis and evaluates the safety and efficacy of short courses of antimicrobial therapy using combined agents for intravaginal use.